PERANCANGAN KOMUNIKASI VISUAL PROMOSI KERAJINAN LAKER PALEMBANG - Galang Sabillah Bahar; Husni Mubarat; Bobby Halim (Besaung : Jurnal Seni Desain dan Budaya, 2021)
Laker is a typical Palembang handicraft in the form of all products or household utensils made of wood, rattan, bamboo or whatever is painted with black ink and then coated with varnish as an ingredient to beautify it as well aspreservative. In this modern era the use of Crafts Laker in palembang is increasingly fading and it's not longer a culture in the City of palembang, especially the younger generation. The lack of promotion carried out on Laker handicrafts has made many of today's young generations not too familiar with Laker crafts, not even a few of them don’t know at all what laker craft is. Moreover, in the current development era, there is a fear of changing cultural heritage forms as a result of the impact of the development and progress of modern technology and other cultural elements that come from outside. To avoid this, visual promotion efforts are needed to the people of Palembang. This promotion was carried out to be able to invite the people of Palembang to cultivate laker crafts in daily life,especially the younger generation. Therefore the Visual Communication Design, Promotion of Laker Crafts is a form of persuasive effort to the people of Palembang, especially to get to know the Laker Crafts so that they can instill a sense of love and pride in Palembang Laker crafts that are known to the Palembang youth, and can invite Palembang people, especially the younger generation cultivate Laker crafts in daily life along with the trends of the times. Keywords : Traditional Craft, Palembang’s Laker, Unique Craft